Perceptions and care Recommendations from Previvors: Qualitative analysis of female BRCA1/2 mutation Carriers' experience with genetic testing and counseling - Kate E. Dibble; Laura K.M. Donorfio; Preston A. Britner; Keith M. Bellizzi (Elsevier, 2022)
Introduction: It is estimated that 12.5% of women will be diagnosed with breast cancer and 1.10% with ovarian cancer during their lifetime. Although less common, women with these mutations have a 11-72% increased risk of breast/ovarian cancers and are hereditary. Genetic testing/counseling presents the opportunity to identify carriers of BRCA1/2 genetic mutations before a cancer diagnosis. Methods: Thirty-four BRCA1/2-positive women (with and without histories of breast/ovarian cancers) were recruited through online national support groups to gain a better understanding of their genetic testing/counseling perceptions and experiences. After confirming eligibility, they were invited to participate in either a telephone or webcam interview. Interview transcripts were analyzed using qualitative thematic text analysis and descriptive coding techniques. Results: Six major themes emerged, capturing the perceptions and experiences of genetic testing/counseling for these women: 1) Emotional Reactions to Results and Genetic Counseling, 2) Future Recommendations, 3) Family Solidarity and Support, 4) Experiences with the Healthcare System, 5) Preventive Concerns and Decisions, and 6) Sources Affecting Perceived Risk. Two subthemes also emerged within the first theme, which are termed "Pre-vivor," and "Testing Intuition." Conclusions: Participants indicated that genetic testing/counseling improvements would be helpful for women in this population surrounding quality care, including sensitivity training for healthcare professionals involved in testing/counseling, additional educational resources, and increased emotional and financial support. Although these recommendations may be beneficial, more widespread research with greater generalizability to disparate groups may be necessary prior to implementation.